Relationship Of Parenting Patterns And Interest Towards Music Learning Outcomes Of Class VIII Students SMP Negeri 2 Brebes - Dewi, Astrio Dinarti Aulia; Aesijah, Siti; Salafiyah, Nafik (Universitas Negeri Semarang, 2021)
The results of study are influenced by some factors. Parenting patterns and learning interests are factors that influence Music learning outcome. The formulation of the problem in this study is (1) whether there is a relationship between parenting patterns on the learning outcomes of Music Arts; (2) whether there is a relationship between interest in the learning outcomes of Music; (3) whether there is a relationship between parenting patterns and interest in the learning outcomes of Music. The purposes of the study were (1)to find out whether there is a relationship between parenting styles and learning outcomes in music; (2) to know whether there is a relationship of interest to the learning outcomes of music; (3) to find out whether there is a relationship between parenting patterns and mutual interest in the results of learning music. The results showed that: (1) there was a positive relationship between parenting style and learning outcomes in Music, with the interpretation of the closeness of the correlation showing a small category, which was 9.48%; (2) there was a positive relationship between interest in the learning outcomes of Music, with the interpretation of the closeness of the correlation indicating the sufficient category, which was 11.42%; (3) there was a positive relationship between parenting and interest in the learning outcomes of Music, with the interpretation of the closeness of the correlation indicating the sufficient category, which was 37.82%. The conclusion of this study was that there was a positive and significant relationship between parenting and interest together on the learning outcomes of Music. The application of parenting with a democratic attitude by paying attention, caring, and respecting children's freedom, as well as guiding with understanding can create conditions for children to study music diligently, both in theory and practice. Thus, children's music learning outcomes can certainly increase.